Toward an improved assessment of quality of life in endometriosis: evaluation of the Spanish version of the Endometriosis Health Profile 30 - Josep Marí-Alexandre; Javier García-Oms; Cristina Agababyan; Rocío Belda-Montesinos; Susana Royo-Bolea; Begoña Varo-Gómez; Cristina Díaz-Sierra; Eva González-Cantó; Juan Gilabert-Estellés (Taylor & Francis Group, 2022)
Purpose Our main objective is to evaluate the psychometric properties of the Spanish version of the EHP-30 questionnaire. The secondary aim is to evaluate the differences in the scores of the core EHP-30 scales between patients with either surgical treatment or conservative management of endometriosis. Methods Cross-sectional study conducted into a tertiary hospital endometriosis reference unit. All patients (n = 223) pre-surgically completed the core EHP-30 questionnaire, the EQ-5D questionnaire (n = 184) and a visual analogue scale (n = 210) for endometriosis-related pain. Demographical and clinical data were recorded. Results Psychometric characteristics of the Spanish core EHP-30 questionnaire were investigated. Statistical analyses confirmed the five-structure factor, a high degree of internal consistency and of item-total correlation for all the assessed items. Convergent validity between EQ-5D and EHP-30 items and between VAS and EHP-30 subscale pain was observed. Additionally, patients with surgical management rendered significantly higher scores in the core EHP-30 subscales "pain" and "control and powerlessness". Conclusions We present the reliability, validity and acceptability of the Spanish core EHP-30 questionnaire, providing clinicians and researchers with an improved tool to assess the endometriosis-related quality of life. Additionally, we show that patients subsidiaries of surgical treatment for endometriosis present with higher pain and powerlessness than those with conservative management.